(untitled) (Applied Biological Research, 2019)
The sedentary lives of macro-invertebrates enable them to act as continuous monitor of water quality of freshwater bodies. Some specific families of benthic macro-invertebrate fauna belonging particularly to the Order Ephemeroptera, Trichoptera, Plecoptera, Hemiptera, Coleoptera, Diptera, Molllusca, Crustacea, Odonata, Hirudinea, Oligochaeta, Polychaeta and Planaria have been recognized as bioindicator of water quality by Biological Monitoring Working Party (BMWP). The present study was carried out to explore the taxonomic richness of macro-zoobenthos found in various habitats and biological water quality of river Ganga in Uttarakhand stretch of India at 3 locations viz., Haridwar barrage, Jagjeetpur sewage treatment plant (STP) upstream and downstream. The samples were collected twice a year to elucidate seasonal variation in taxa occurrence. A total of 1,560 individuals belonging to 32 families and 12 taxonomic orders were recorded. Biological water quality at Haridwar barrage was found to be clean in both the seasons. Direct discharge of untreated sewage from Jagjeetpur STP had profound effect on the biota of river and lead to community replacement at downstream of discharge. Dominant Ephemeroptera colonies were replaced by Diptera family Chironomidae at this location and thereby showed decline in biological water quality.